Plasma radiation behavior approaching high-radiation scenarios in W7-X. (25th October 2021) - Zhang, D.; Burhenn, R.; Feng, Y.; König, R.; Buttenschön, B.; Beidler, C.D.; Hacker, P.; Reimold, F.; Thomsen, H.; Laube, R.; Klinger, T.; Giannone, L.; et al.
Abstract: The W7-X stellarator has so far performed experiments under both limiter and divertor conditions. The plasma is mostly generated by ECR-heating with powers up to 6.5 MW, and the plasma density is usually limited by the radiation losses from low-Z impurities (such as carbon and oxygen) released mainly from the graphite targets. The present work first summarizes the radiation loss fractions f rad achieved in quasi-stationary hydrogen plasmas in both operational phases, and then shows how impurity radiation behaves differently with the two different boundary conditions as the plasma density increases. The divertor operation is emphasized and some beneficial effects (with respect to impurity radiation) are highlighted: (1) intensive radiation is located at the edge ( r / a > 0.8) even at high radiation loss fractions, (2) the plasma remains stable up to f rad approaching unity, (3) the reduction in the stored energy is about 10% for high f rad scenarios. Moreover, effects of wall boronisation on impurity radiation profiles are also presented.